Random Lasing with a High Quality Factor over the Whole Visible Range Based on Cascade Energy Transfer. Issue 1 (2nd December 2013) - Shi, Xiaoyu; Wang, Yanrong; Wang, Zhaona; Wei, Sujun; Sun, Yanyan; Liu, Dahe; Zhou, Jing; Zhang, Yongyi; Shi, Jinwei
<x xml:space="preserve">Abstract</x> On the basis of cascade energy transfer between different dye molecules, single‐excitation and low threshold coherent random lasing with a high quality factor (∼13 000) over the whole visible range is experimentally observed using gold–silver bimetallic porous nanowires with abundant nanogaps as the scatterers. These nanogaps with different sizes in the bimetallic nanowires can produce continuous plasmonic resonance spectra and provide strong feedback or gain channels for the stimulated emission from different dye molecules. It guarantees a low threshold of lasing. Moreover, multi gain media can provide broad tunability of the emission wavelength when the system is pumped by single‐wavelength pulses. It provides excellent flexibility for the design of multicolor output devices.